Dynamics of fishery and distribution of aggregations for saffron cod Eleginus gracilis (Tilesius) at northern Kuril Islands - О. V. Novikova (Известия ТИНРО)
The fishery on winter-spring accumulations of saffron cod in the area of northern Kuril Islands has a long history with varying intensity, though this species is not abundant both in the Pacific and Okhotsk Sea waters of this area. The annual catch ranged from 1.8 to 167.4 t in 2003–2022, on average 40.8 t/yr. The fish with length of 24–56 cm were presented in commercial catches of Danish seine, with prevalence of the 36–48 cm size group. The average length of saffron cod in the catches was changed from 35.4 cm in summer to 43.2 cm in winter that coincided with the fishing depth increasing in winter. The main commercial concentrations of the species had formed between the islands of Paramushir and Shumshu and in the area of the First Kuril Strait.